Designing an information system for incoming and outgoing mail at the sukaraja village head office prabumulih selatan district - niko alwariando niko alwariando; Meilyana Winda Perdana (International Journal Cister, 2022)
The archives at the Sukaraja village head office in the south prabumulih sub-district have not been neatly organized, there are still missing equipment, archive storage does not match the disposition number and letters are also often included in other orders. when looking for the desired letter, it must take a long time and the letter becomes damaged or torn because it does not match the disposition serial number. File cabinets are often not neatly organized, so it takes time to find the letters you need. Letter archives are also often borrowed by other departments but archivists never record who borrows, when to borrow and what needs to be borrowed. Therefore, letter files are often lost.